Cover Picture: Monolithic Composite Electrodes Comprising Silicon Nanoparticles Embedded in Lignin‐derived Carbon Fibers for Lithium‐Ion Batteries (Energy Technol. 9/2014). Issue 9 (October 2014) - Rios, Orlando; Martha, Surendra K.; McGuire, Michael A.; Tenhaeff, Wyatt; More, Karren; Daniel, Claus; Nanda, Jagjit
<x xml:space="preserve">Abstract</x> Lignin–silicon electrodes—The best of both worlds: The cover image highlights a method that combines lignin‐derived carbon fibers with silicon nanoparticles to form novel electrodes for high‐capacity lithium‐ion batteries. Silicon is viewed as an attractive anode material because of its high theoretical capacity, but when used in bulk or film forms, silicon suffers from mechanical degradation and loss of electrical conductivity during battery cycling. The Communication by Orlando Rios and colleagues at Oak Ridge National Laboratory and the Indian Institute of Technology on page 773 introduces a direct manufacturing process to encapsulate the active silicon particles within melt‐spun carbon fibers made from lignin. The new low‐cost composite material exhibits nearly twice the capacity of graphitic carbon commonly used in lithium‐ion batteries.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>